2008
DOI: 10.1016/j.ejvs.2008.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Morphology Following Endovascular Repair of Acute and Chronic Type B Aortic Dissection: Implications for Management

Abstract: The data support the use of endovascular repair of the thoracic aorta in Type B aortic dissection. 30-d outcomes are acceptable. Patients with AAD demonstrate significant aortic remodelling whereas patients with CAD do not. This has significant implications for practice as patients with CAD must rely on maintenance of false lumen thrombosis to preserve the integrity of the endovascular repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
115
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(128 citation statements)
references
References 18 publications
8
115
3
2
Order By: Relevance
“…19,28 However, open surgery offers a robust solution to preventing aortic-related death over long-term follow-up, 29 whereas the outcome after endovascular therapy is not as well defined, with uncertainty over the morphology of the distal aorta after TEVAR. 30 The present study has revealed that patients with both acute and chronic aortic dissection have low rates of aortic-related mortality in the midterm after TEVAR. After the initial perioperative phase, aortic-related mortality is low, which suggests that endovascular therapy has the potential to confer prevention of aortic dissection and rupture over a reasonable time period.…”
Section: Discussionmentioning
confidence: 89%
“…19,28 However, open surgery offers a robust solution to preventing aortic-related death over long-term follow-up, 29 whereas the outcome after endovascular therapy is not as well defined, with uncertainty over the morphology of the distal aorta after TEVAR. 30 The present study has revealed that patients with both acute and chronic aortic dissection have low rates of aortic-related mortality in the midterm after TEVAR. After the initial perioperative phase, aortic-related mortality is low, which suggests that endovascular therapy has the potential to confer prevention of aortic dissection and rupture over a reasonable time period.…”
Section: Discussionmentioning
confidence: 89%
“…Following coverage of the primary entry tear in ATBAD, there is rapid aortic remodelling with an increase in diameter of the TL and a reduction in FL diameter. 91,192 By contrast, in chronic dissections, there is less aortic remodelling and the integrity of the endovascular repair is determined by the ability of the endovascular procedure to induce FL thrombosis. In treating chronic dissections, it has been shown that FL thrombosis occurs more often in patients with limited dissection and that FL thrombosis occurs more effectively in the stented part of the DTA.…”
Section: Recommenda On 37mentioning
confidence: 99%
“…Irrespective of the extent of aortic coverage, the dissected portion of the aorta below the diaphragm remains untreated, and there is evidence to suggest that this region may dilate over time. 91 The role of bare stents in the treatment of chronic dissection, and the effect that these stents have on aortic remodeling, remain undefined at the present time. 99 The available literature regarding TEVAR for chronic dissection in patients with MFS is sparse.…”
Section: Recommenda On 37mentioning
confidence: 99%
“…Our patient had a rare true aneurysm similar to a dissecting aneurysm [7] . Usually, dissecting aneurysm is caused by an intimal tear or interstitial hemorrhage and requires emergency surgery, and has a low survival rate.…”
Section: Discussionmentioning
confidence: 99%